Violence and memory in John Ruganda's The Burdens and The Floods. - Sambai, Carolyn Sultan Chebet (My University, 2009)
ABSTRACT This research report is an investigation of the theme of violence and the use of memory in John Ruganda’s two plays: The Floods and The Burdens. This study examines the representation of a historic period in Uganda’s history as represented in Ruganda’s two plays. The study focuses on the reign of Idi Amin, Uganda’s former dictator. It gives a detailed examination of the use of violence by the state as a tool for achieving and maintaining power. I argue that the totalitarian state uses violence to assert its power and to eliminate its enemies. I also examine how Ruganda represents Idi Amin’s regime in The Floods, focusing on various forms of violence and how he uses the setting of the play, characterization and dialogue to highlight the extent of violence in the regime. The first chapter gives the background of the study focusing on the social and political contexts in which the plays were set. The second chapter deals with violence both by the state and violence in the private space in The Burdens which deploys the space of the family to critique violence by the state. In this chapter, I also discuss the politics of dead bodies. Here I argue that the desire of the state to stay in power does not end at controlling the people while they are alive but that it includes how dead bodies are (mis) treated. In the final chapter I discuss the role of memory in the two plays. I argue that in The Burdens, memory is an escape zone where characters hide from their unpleasant present. In The Floods, I try to show how memory forms part of the narrative of the play in that characters retell their experiences for purposes of unfolding ‘facts’ about the regime.